2014
DOI: 10.3324/haematol.2013.095604
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genome-wide genotyping and gene expression profiling reveals BCL11B as a putative oncogene in acute myeloid leukemia with 14q32 aberrations

Abstract: ABSTRACTnucleotide polymorphism arrays is the fact that allele losses are directly recognizable as loss-of-heterozygosity. In fact, single nucleotide polymorphism arrays revealed that approximately 20% of cases of AML exhibit large nonrandom regions of homozygosity without changes in copy number as a result of segmental uniparental disomy, often indicating mutations in genes within these regions. These areas of uniparental disomy have been associated with mutations in CEBPA, WT1, FLT3 and RUNX1. 15,16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
(66 reference statements)
0
23
0
Order By: Relevance
“…In fact, the formation of super-enhancers in translocations may be a more common mechanism by which oncogenes are activated in AML and other types of cancer. In support of this, we recently showed that transposition of the B-Cell CLL/Lymphoma 11B (BCL11B) transcription factor locus into well-known super-enhancers resulted in overexpression of the BCL11B gene in several cases of AML (Abbas et al, 2014).…”
Section: Aberrant Evi1 Expression In Inv(3)/t(3;3) Aml and Cooperatinmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, the formation of super-enhancers in translocations may be a more common mechanism by which oncogenes are activated in AML and other types of cancer. In support of this, we recently showed that transposition of the B-Cell CLL/Lymphoma 11B (BCL11B) transcription factor locus into well-known super-enhancers resulted in overexpression of the BCL11B gene in several cases of AML (Abbas et al, 2014).…”
Section: Aberrant Evi1 Expression In Inv(3)/t(3;3) Aml and Cooperatinmentioning
confidence: 88%
“…In support of this, we recently showed that transposition of the B-Cell CLL/Lymphoma 11B (BCL11B) transcription factor locus into well-known super-enhancers resulted in overexpression of the BCL11B gene in several cases of AML (Abbas et al, 2014). In fact, the formation of super-enhancers in translocations may be a more common mechanism by which oncogenes are activated in AML and other types of cancer.…”
Section: Aberrant Evi1 Expression In Inv(3)/t(3;3) Aml and Cooperatinmentioning
confidence: 90%
“…The pro-tumorigenic role of the ZEB2-BCL11B fusion has been previously linked to the overexpression of BCL11B [28,40]. Paraffin-embedded tissue was available for one of the patients carrying the chimera (#59810) and BCL11B expression was confirmed at protein level by immunohistochemistry ( Figure 3B).…”
Section: Bcl11b Protein Expression In Aml and Its Transcriptional Sigmentioning
confidence: 91%
“…In humans, chromosomal translocations involving the BCL11b gene locus were identified in patients with acute myeloid leukemia (AML), T-ALL and T/myeloid acute bilineage leukemia [[23]–[28]]. Likewise, deletions and missense mutations, disrupting gene function, were reported in 9 to 16% of pediatric T-ALL patients [[29],[30]].…”
Section: Introductionmentioning
confidence: 99%